Social resilience and civic entrepreneurship in self-help organizations : case study of the Kibera slum project - Kuusikko, Noora (2011)
The aim of this study is to explore social resilience and civic entrepreneurship in self-help organizations. The purpose is to find out how social resilience can be built through entrepreneurial activities. The issue is explored in a self-help organization in the Kibera slum. The intention is to contribute on the discussion on the best practises of self-help organization and the key elements behind their success or failure in developing countries. The thesis is divided into two main parts: the first one presents the key terms and a literary review on the concepts of social resilience and civic entrepreneurship. The second part is a case study on the cooperation of two non-governmental organizations in Nairobi Kibera. The two organizations are a local self-help organization Drug Fighters and Councelling for Young Generation (DFC) and a Finnish development organization Mikkeli Fair Trade Association (Kema). The second part of the study is originally written as a base-line study to the financer organization. Other area of interest in this study is networking, which is inevitable for building social resilience in small self –help organization in the slum. The findings of this study indicate that major reasons behind DFC’s success are the entrepreneurial skills of the director and founder of the organization. The organization contributes effectively to community resilience. It became evident that without social resilience it would be impossible for an organization to survive in the slum environment. In building social resilience the creative thinking and civic entrepreneurship are essential.